2020
DOI: 10.1029/2020ef001668
|View full text |Cite
|
Sign up to set email alerts
|

Global Spatio‐Temporal Assessment of Changes in Multiple Ecosystem Services Under Four IPCC SRES Land‐use Scenarios

Abstract: Social development and technological advancement have led to land use changes, influencing the structure of ecosystem services and severely impacting ecological balance. This study spatially and quantitatively assesses the effects of land-use changes on ecosystem services based on the fourth assessment report of the Intergovernmental Panel on Climate Change (IPCC) and using the Integrated Valuation of Ecosystem Services and Tradeoff (InVEST) model. This model, applied on a global scale, was used to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 41 publications
(45 reference statements)
3
7
0
Order By: Relevance
“…For the SR model, this stu previous studies have calculated that the soil and water conservation volume of River Valley (based on actual measurements) was 2.64 × 10 8 tons [53], which is con This effect may also be related to the amount of nitrogen retained by the vegetation, which is consistent with the findings of Sun [48]. In this study, WY and SR were positively correlated with synergistic effects, which is consistent with the findings of Sun and Shi [54]. When forests are converted to grassland, farmland, and construction land, they have greater evapotranspiration, retention, and evaporation than grasses or crops, thus reducing water production [64].…”
Section: Model Validationsupporting
confidence: 91%
See 2 more Smart Citations
“…For the SR model, this stu previous studies have calculated that the soil and water conservation volume of River Valley (based on actual measurements) was 2.64 × 10 8 tons [53], which is con This effect may also be related to the amount of nitrogen retained by the vegetation, which is consistent with the findings of Sun [48]. In this study, WY and SR were positively correlated with synergistic effects, which is consistent with the findings of Sun and Shi [54]. When forests are converted to grassland, farmland, and construction land, they have greater evapotranspiration, retention, and evaporation than grasses or crops, thus reducing water production [64].…”
Section: Model Validationsupporting
confidence: 91%
“…This effect may also be related to the amount of nitrogen retained by the vege which is consistent with the findings of Sun [48]. In this study, WY and SR were pos correlated with synergistic effects, which is consistent with the findings of Sun a [54]. When forests are converted to grassland, farmland, and construction land, the greater evapotranspiration, retention, and evaporation than grasses or crops reducing water production [64].…”
Section: Trade-off Effects Between Esssupporting
confidence: 89%
See 1 more Smart Citation
“…Ecological corridors are important links between the structure and function of a system, and grasslands can be used as buffer zones to improve the connectivity of ecological functions, allowing species to use corridors for long-distance dispersal or to provide shelter for some animal movements [ 129 ], thus maintaining and protecting biodiversity and improving the quality of their habitats [ 130 , 131 ]. At the same time, the spatial pattern of the landscape influences the magnitude of ecosystem service provision at the landscape scale through grassland use patterns and connectivity [ 132 , 133 , 134 , 135 ]. By quantifying inter-annual and seasonal changes in grassland landscape patterns in northern China, Hao et al showed that degraded vegetation can influence changes in ecosystem service functions by changing land use patterns, increasing or dividing patch sizes of grassland and agricultural land, and increasing the size of forest areas where appropriate [ 136 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing the demands of different cities could help policymakers choose an optimal urbanization model and land use pattern for improving CS ( Gao & Wang, 2019 ; Nie et al, 2020 ). Scenario settings are useful tools for predicting the future impacts of LULC changes on CS and can be used to produce critical information for urban development and planning ( Sun & Shi, 2020 ; Tang et al, 2020 ). However, previous studies predicting changes in LULC have had some limitations.…”
Section: Introductionmentioning
confidence: 99%